2015
DOI: 10.1002/gepi.21901
|View full text |Cite
|
Sign up to set email alerts
|

Kernel Approach for Modeling Interaction Effects in Genetic Association Studies of Complex Quantitative Traits

Abstract: The etiology of complex traits likely involves the effects of genetic and environmental factors, along with complicated interaction effects between them. Consequently, there has been interest in applying genetic association tests of complex traits that account for potential modification of the genetic effect in the presence of an environmental factor. One can perform such an analysis using a joint test of gene and gene-environment interaction. An optimal joint test would be one that remains powerful under a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Detailed proofs are in Supplementary Materials. Following the Previous works 11 13 , 15 , 21 24 , test statistics of the FGE-SKAT are based on the second term of the likelihood function.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed proofs are in Supplementary Materials. Following the Previous works 11 13 , 15 , 21 24 , test statistics of the FGE-SKAT are based on the second term of the likelihood function.…”
Section: Methodsmentioning
confidence: 99%
“…Tests for gene-environment interactions using one SNP and one environmental factor have been proposed 14 . For better statistical power, such types of interactions using genomic regions are also discussed 15 , 16 . Recent studies also showed surprising findings with gene-environment interactions 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Lin, Lee, Christiani, and Lin (2013) proposed aggregative GxE testing by treating the main genetic and environmental effects as fixed and testing the significance of random GxE interaction effects using a score test. Broadaway et al (2015) provided an alternative formulation of GESAT, which jointly tests the genetic, environmental, and GxE interaction effects using the joint weighted two-way interaction kernel. Kernel methods outside of the kernel regression framework, such as kernel canonical correlation analysis (Larson et al, 2014;Yuan et al, 2012), have also been developed for GxG association analyses in case-control studies.…”
Section: Interaction Testingmentioning
confidence: 99%
“…A variance component score test is usually used for statistical significance. In the problem of testing the overall genetic effect, a two‐way interaction kernel has been used that showed improved power compared to traditional joint testing (Broadaway et al, ).…”
Section: Introductionmentioning
confidence: 99%